2016
DOI: 10.1534/genetics.115.183020
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Dysfunction Triggers Palindrome Formation Independently of Double-Strand Break Repair Mechanisms

Abstract: Inverted chromosome duplications or palindromes are linked with genetic disorders and malignant transformation. They are considered by-products of DNA double-strand break (DSB) repair: the homologous recombination (HR) and the nonhomologous end joining (NHEJ). Palindromes near chromosome ends are often triggered by telomere losses. An important question is to what extent their formation depends upon DSB repair mechanisms. Here we addressed this question using yeast genetics and comparative genomic hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Evidence for fold-back inversions has been found in the genomes of viruses (28), prokaryotes (29), is associated with genetic disease (22,30,31) and a variety of cancers (32-34) Moreover, fold-back inversions observed in human cancer cells having escaped telomere-driven crisis occur independently of DSB repair (35,36), consistent with our findings. Thus, we anticipate that this study will contribute to the understanding of rapid genome evolution, pathogenesis and tumorigenesis.…”
supporting
confidence: 90%
“…Evidence for fold-back inversions has been found in the genomes of viruses (28), prokaryotes (29), is associated with genetic disease (22,30,31) and a variety of cancers (32-34) Moreover, fold-back inversions observed in human cancer cells having escaped telomere-driven crisis occur independently of DSB repair (35,36), consistent with our findings. Thus, we anticipate that this study will contribute to the understanding of rapid genome evolution, pathogenesis and tumorigenesis.…”
supporting
confidence: 90%
“…The palindromic analysis of discrete sequences has partly revolutionized molecular biology and is widely used as shown by the following work [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ], to name a few. Very recently, the study of quantum behavior [ 9 ], encountered in palindromes within the DNA structure, revealed that the symmetry properties of the unitary structure, other than those present in classical palindromes, play an important role in the origin and cause of mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have shown that these palindromic oligonucleotides have remarkable immunogenetic properties and potantiate the induction of interferon release from natural killer cells [7,8]. However, above all the explanations regarding the functionality of palindrome, the best approach may be the ability of these specific sequences to form hairpin [9]. Nag and Kurst revealed that palindromic sequences present breakpoints during the cellular process which requires double-strand breaks such as meiosis [10].…”
Section: Introductionmentioning
confidence: 99%